The Case for a European Banking Charter - Cihak, Martin (IMF Working Papers; Working Paper, 2007)
Most financial institutions in the European Union (EU) are still based in one country, but a number of large financial institutions (LCFI) have systemic cross-border exposures. The paper explains how, despite much progress, nationally-segmented supervisory frameworks and national accountability for financial stability hinder optimization across borders of banks' operations and efficient and effective LCFI supervision. A full-fledged EU-level prudential regime that operates along-side national regimes--a European Banking Charter (EBC)--could harness market forces to establish a level playing field for financial sector competition, while plugging some significant gaps in Europe's financial stability framework without concentrating excessive powers.